Ketika Demokrasi Membutuhkan Inklusi - Sylvester Kanisius Laku (Gerakan Indonesia Kita, 2021)
Democracy is a political tool that aims to reach agreement and produce fair decisions for everyone. However, it seems that not all democratic processes and decision-making involve individuals or groups who are socially in a weak, powerless, and marginalized position. These groups, such as women, the elderly, minority groups, and the poor, find themselves in a disadvantageous situation, while political decisions made through a democratic process also impact and affect them directly. Based on this thought, Iris Marion Young, a modern feminist political thinker, seeks to dismantle the various democratic symptoms that obstruct the achievement of justice for all. One of the main problems Young identified is the attempt by those in power to ignore or override the role of communities that are not in power, thereby preventing them from taking full part in democratic processes and decision-making. Therefore, Young proposes the need to intrude on inclusion in the democratic process, through communication models which she calls communicative democracy.